2019
DOI: 10.3390/buildings9010012
|View full text |Cite
|
Sign up to set email alerts
|

Physical vs. Aesthetic Renovations: Learning from Swedish House Owners

Abstract: In this paper, we identify the socio-economic attributes and attitudes that have influenced house owners in renovating their homes in the past. Our study is based on responses to an online questionnaire survey of 971 house owners living in Kronoberg County in Sweden. Results showed that the interest and willingness of the house owners to perform a renovation varied depending on their demographic background and the age of the house. The latter positively affected past renovations, only when combined with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Using the Internet to conduct survey questionnaires is a common and increasingly utilized approach [39,44], as it is generally a faster method of collecting data when compared to administering printed surveys [45][46][47] and is generally less expensive [35]. As Collins [48] observed, survey questions should be kept short and to the point.…”
Section: Stage 2: Internet-based Surveymentioning
confidence: 99%
“…Using the Internet to conduct survey questionnaires is a common and increasingly utilized approach [39,44], as it is generally a faster method of collecting data when compared to administering printed surveys [45][46][47] and is generally less expensive [35]. As Collins [48] observed, survey questions should be kept short and to the point.…”
Section: Stage 2: Internet-based Surveymentioning
confidence: 99%
“…The inadequate adoption of energy efficient measures by the house owners is a subject widely examined in the literature. Several studies identify the factors motivating or preventing house owners from adopting such measures (e.g., [27,[29][30][31][32][33][34][35][37][38][39][40][41]). In general, the decision of house owners regarding energy efficiency related renovations is the outcome of different factors, which can act either as motives or as barriers for those decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There exist several studies on house owners' decision-making towards renovations [29][30][31][32][33][34]. Each of these studies apply to specific contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Trends, status and lifestyles are factors this author also refers as boosters to renovation. Bravo et al [31] demonstrated that renovation works are normally linked to aesthetic aspects of the house.…”
Section: Social Science In Energy Research: Recent Evidencementioning
confidence: 99%